Comparative functional analyses of DWARF14 and KARRIKIN INSENSITIVE 2 in drought adaptation of Arabidopsis thaliana. (17th March 2020) - Li, Weiqiang; Nguyen, Kien Huu; Chu, Ha Duc; Watanabe, Yasuko; Osakabe, Yuriko; Sato, Mayuko; Toyooka, Kiminori; Seo, Mitsunori; Tian, Lei; Tian, Chunjie; Yamaguchi, Shinjiro; Tanaka, Maho; et al.
SUMMARY: Functional analyses of various strigolactone‐deficient mutants have demonstrated that strigolactones enhance drought resistance; however, the mechanistic involvement of the strigolactone receptor DWARF14 (D14) in this trait remains elusive. In this study, loss‐of‐function analysis of the D14 gene in Arabidopsis thaliana revealed that d14 mutant plants were more drought‐susceptible than wild‐type plants, which was associated with their larger stomatal aperture, slower abscisic acid (ABA)‐mediated stomatal closure, lower anthocyanin content and delayed senescence under drought stress. Transcriptome analysis revealed a consistent alteration in the expression levels of many genes related to the observed physiological and biochemical changes in d14 plants when compared with the wild type under normal and dehydration conditions. A comparative drought resistance assay confirmed that D14 plays a less critical role in Arabidopsis drought resistance than its paralog karrikin receptor KARRIKIN INSENSITIVE 2 (KAI2). In‐depth comparative analyses of the single mutants d14 and kai2 and the double mutant d14 kai2, in relation to various drought resistance‐associated mechanisms, revealed that D14 and KAI2 exhibited a similar effect on stomatal closure. On the other hand, D14 had a lesser role in the maintenance of cell membrane integrity, leaf cuticle structure and ABA‐induced leaf senescence, but a greater role in drought‐induced anthocyanin biosynthesis, than KAI2. Interestingly, a possible additive relationship between D14 and KAI2 could be observed in regulating cell membrane integrity and leaf cuticle development. In addition, our findings also suggest the existence of a complex interaction between the D14 and ABA signaling pathways in the adaptation of Arabidopsis to drought. Significance Statement: The signaling pathways mediated by two paralogous proteins, the strigolactone receptor DWARF14 and the karrikin receptor KARRIKIN INSENSITIVE 2, show both overlapping and specific responses in affecting various physiological and biochemical processes to positively modulate Arabidopsis adaptation to drought. Data obtained from the transcriptome analysis support our findings at a molecular level.